Demographic characteristics and mortality of dengue fever in Medan City (2021-2024) - Iqbal, Muhammad; Silalahi, Marlinang Isabella; Pane, Putri Yunita; Sibagariang, Eva Ellya; Munthe, Dewi Sartika; Nardi, Leo; Fransiskus, Antonius; Lawrence, Christopher; Ongko, Nicolas Xavier (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2025)
Dengue Hemorrhagic Fever (DHF) is a significant public health challenge in Indonesia, including the city of Medan. This study aimed to determine the prevalence, demographic distribution (by sex and age group), and mortality rates of DHF in Medan from 2021 to 2024. This study used secondary data from reports provided by the Medan City Health Office, which compiled information from all public health centers (Puskesmas) in the region. Analysis of the data revealed that the pediatric age group (5–14 years) was the most affected population. The distribution of cases showed a relatively balanced proportion between males and females. DHF mortality rates fluctuated annually, with a notable downward trend observed in 2024. These findings underscore the critical need to strengthen DHF prevention and control programs, with a specific focus on vulnerable age groups and high-incidence areas. This study is expected to serve as a foundational resource for public health policy planning and to enhance the capacity of primary healthcare services to effectively manage DHF cases.